An evergreen neotropical savanna tree (Gochnatia polymorpha, Asteraceae) produces different dry- and wet-season leaf types - Rossatto, Davi R. [UNESP]; Kolb, Rosana Marta [UNESP] (CSIRO Publishing, 2009)
Gochnatia polymorpha (Less.) Cabrera is a widespread tree species found in different physiognomies of neotropical savanna (cerrado) formations of south-eastern Brazil. The present study describes some leaf anatomical characteristics of this species as a function of the time of leaf flush, during dry or wet seasons. This species presents anatomical plasticity in the cuticle, palisade parenchyma and abaxial epidermis as well as in stomatal size and stomatal and trichome density, which are leaf structures linked with water-status control. Leaf structure changed to suit the particular environmental conditions during dry and wet seasons. The production of different wet-and dry-season leaf types in G. polymorpha could be a response to drought and an adaptation to environmental constraints in the cerrado.